The phenylmethylthiazolylthiourea nonnucleoside reverse transcriptase (RT) inhibitor MSK-076 selects for a resistance mutation in the active site of human immunodeficiency virus type 2 RT. - Auwerx, J; Stevens, M; Van Rompay, A; Bird, L; Ren, J; De Clercq, E; Oberg, B; Stammers, D; Karlsson, A; Balzarini, J (2004)
The phenylmethylthiazolylthiourea (PETT) derivative MSK-076 shows, besides high potency against human immunodeficiency virus type 1 (HIV-1), marked activity against HIV-2 (50% effective concentration, 0.63 microM) in cell culture. Time-of-addition experiments pointed to HIV-2 reverse transcriptase (RT) as the target of action of MSK-076. Recombinant HIV-2 RT was inhibited by MSK-076 at 23 microM. As was also found for HIV-1 RT, MSK-076 inhibited HIV-2 RT in a noncompetitive manner with respect to dGTP and poly(rC).oligo(dG) as the substrate and template-primer, respectively. MSK-076 selected for A101P and G112E mutations in HIV-2 RT and for K101E, Y181C, and G190R mutations in HIV-1 RT. The selected mutated strains of HIV-2 were fully resistant to MSK-076, and the mutant HIV-2 RT enzymes into which the A101P and/or G112E mutation was introduced by site-directed mutagenesis showed more than 50-fold resistance to MSK-076. Mapping of the resistance mutations to the HIV-2 RT structure ascertained that A101P is located at a position equivalent to the nonnucleoside RT inhibitor (NNRTI)-binding site of HIV-1 RT. G112E, however, is distal to the putative NNRTI-binding site in HIV-2 RT but close to the active site, implying a novel molecular mode of action and mechanism of resistance. Our findings have important implications for the development of new NNRTIs with pronounced activity against a wider range of lentiviruses.